Levels of anxiety in women aged ≥45 years undergoing diagnostic large loop excision of the transformation zone: A longitudinal study. (13th October 2022) - Gustafson, Line Winther; Larsen, Mette Bach; Hammer, Anne; Petersen, Lone Kjeld; Andersen, Berit; Bor, Pinar
Abstract: Objective: To measure anxiety levels in women aged ≥45 years undergoing diagnostic large loop excision of the transformation zone (LLETZ) at the first colposcopy visit. Design: Longitudinal study. Setting: Three colposcopy clinics in the Central Denmark Region. Population: Women aged ≥45 years undergoing diagnostic LLETZ. Methods: Women completed the State–Trait Anxiety Inventory (STAI) and Short Form 12 (mental and physical health) questionnaires before, immediately after, and at 1 and 6 months after LLETZ. Main outcome measures: STAI state anxiety median scores were calculated and stratified by health status, by letter with information about screening result and by LLETZ results. Results: Of 109 eligible women, 11 were excluded, leaving 98 women for the final analyses. Response rates ranged from 84.7% to 100%. Overall, state anxiety levels were low; however, a decrease was observed from before to immediately after the LLETZ (33.4 vs 29.3, p < 0.001). The anxiety levels remained stable up to 6 months after LLETZ. Women with poor mental health were more likely to have higher anxiety levels compared with women with good mental health (before LLETZ, RR 3.77, 95% CI 2.12–6.70; 1 month after LLETZ, RR 3.37, 95% CI 1.59–7.15; 6 months after LLETZ, RR 1.93, 95%CI 1.06–3.51). Conclusions: Overall, colposcopy and diagnostic LLETZ in women aged ≥45 years were not associated with high levels of anxiety. Anxiety levels were highest before colposcopy, and the women seemed to experience immediate relief afterwards. Women with poor mental health had the highest anxiety levels throughout the study, which might call for special attention. Abstract : Linked article : This article is commented on by Margaret Cruickshank, pp. 201 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.17336 .